Minireview on Novel Anti-infectious Treatment Options and Optimized Drug Regimens for Sepsis - Hites, Maya (Frontiers in Medicine, 2021)
Sepsis, a life-threatening organ dysfunction caused by a dysregulated response to infection is a major public health concern, as it is a leading cause of mortality and critical illness worldwide. Antibiotics are one of the cornerstones of the treatment of sepsis; administering appropriate antibiotics in a rapid fashion to obtain adequate drug concentrations at the site of the infection can improve survival of patients. Nevertheless, it is a challenge for clinicians to do so. Indeed, clinicians today are regularly confronted with infections due to very resistant pathogens, and standard dosage regimens of antibiotics often do not provide adequate antibiotic concentrations at the site of the infection. We provide a narrative mini-review of different anti-infectious treatments currently available and suggestions on how to deliver optimized dosage regimens to septic patients. Particular emphasis will be made on newly available anti-infectious therapies.